How many cervical cancer cases can potentially be prevented using a more sensitive screening test at young age?. Issue 2 (5th August 2013) - de Kok, Inge M.C.M.; van Rosmalen, Joost; Rozemeijer, Kirsten; Penning, Corine; van Ballegooijen, Marjolein
Abstract : The human papilloma virus (HPV) DNA test has higher sensitivity than cytology for cervical cancer screening. Therefore, cervical cancer cases that are missed by cytology could potentially be identified if we use primary HPV testing. Studies showed that HPV screening is the preferred primary test at age 35 and over. Given the high prevalence of harmless HPV infections, the use of HPV testing at younger age is less obvious. The number of cancers in young age is often mentioned to indicate the possible benefits of a more sensitive test. We actually estimated the proportion of those cases that is potentially preventable in The Netherlands by the use of a more sensitive screen‐test at the first screening age 30, given that the more sensitive test is used at age 35 and over. We analysed the screening history of women diagnosed with cervical cancer in the period 2004 to March 2009, using data from the Dutch National Pathology Registry. Only 15–30% (two to four cases per 100, 000 women) of the cases was preceded by negative cytology under age 35 and therefore could have been prevented by a more sensitive test at age 30. The lower the screening coverage and the shorter the screening interval in those screened at young age, the smaller the gain of a more sensitive test. So, as long as the current screening pattern is not changed, the majority of the cervical cancer cases at young age would still occur even when applying a more sensitive test at the younger ages. Abstract : What's new? For cervical cancer screening, HPV testing is more sensitive than the Pap smear, but at what age is it useful? In this study, the authors evaluated the screening history of Dutch women with cervical cancer to determine how often an HPV test would have helped. Because 15 years can pass between detection of initial lesions and diagnosis of cancer, they counted how often diagnosed occurred within 15 years of a normal Pap smear, when the more sensitive test might have caught an early stage neoplasia. They found that in most cases, the HPV test would not have prevented the cancer.